Hubungan Sikap Ibu Tentang Kesulitan Makan Dengan Status Gizi Anak Usia Pra Sekolah (3-6 Tahun) Di Desa Wonosari Ngoro Mojokerto - Nurun Ayati Khasanah (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2014)
Many children have problems for eating. These problems happen in 25% childrend of Indonesia. It will increase for about 40-70% to children who got premature or cronic disease. Picky Eaters Clinic had done a research on the day priour to 2007. This research said that the children who is 3-6 years or preschool, is gotten 33,6% prevalent problem of eating. This problem will spoil their growth and development of children. The goal of this research knows the relation between what will mother do for nutrient problem of children preschool or (3-6 tahun) in wonosari ngoro mojokerto.This research is observation of analitic, besides make a list with cross sectional. Independent of variable is what will mother do about the problem for eating in children before they get formal education (3-6 years). Variable dependent is nutrient of children preschool (3-6 tahun). Popualtion is fifty eight mothers and their childrend (3-6 years) in Wonosari, Ngoro, Mojokerto. Fifty one person had been the sample by simple random sampling. The statistic test, chi square test had been gotten the sig result. (2 tailed)=0,000<_a=0,05. Its mean there is relation mother do about eating problem with nutrient in children (3-6 years) in wonosari, ngoro , mojokerto.Finally, this research has the result that there is connetion mother do with eating problem that happen in children preschool or 3-6 years in wonosari, ngoro, mojokerto. Because of this result, the medicals personel are expected to increase to give conseling for mother about how to overcome eating problem or the difficulties to eat for children